The Reality of Extension Works in the Directorate of Agricultural Extension and Agricultural Research In Kurdistan Region of Iraq - Hameed, Ahmed Sajid (UHD Journal of Science and Technology, 2024)
The study aims to identify the reality of extension works in the Directorate of Agricultural Extension and Agricultural Researches in the Kurdistan region of Iraq, and the study area included all governorates of the Kurdistan Region of Iraq (Germian, Erbil, Sulaymaniyah, Dohuk). The research community included all workers in agricultural extension, agricultural research, and agricultural directorates in all governorates, there were 215 respondents. The sample of the respondents includes (71) representing 33% of the population, taken by a simple random sampling method. The data were collected through personal interviews; questionnaire was prepared for this purpose. To confirm the validity, the questionnaire was reviewed by some experts. In general, the reality of extension work was described by the respondents (extension workers and agricultural engineers working in the Agricultural Research and Extension Directorate) as weak. Conducting training courses for agricultural extension workers regarding methods and methods of communication to work with farmers, emphasizing the importance and necessity of linking and coordinating between agricultural extension and education (universities) to graduate a qualified agricultural guide. Cooperation with other research agencies that work on producing and generating agricultural scientific information and practices approved by the Ministry of Agriculture.